AUDIT SISTEM INFORMASI AKUNTANSI BERBASIS KOMPUTER - Yani, Ahmad (www.bsi.ac.id, 2009)
Audit Information System Accounting bases on computer is a systematic process for in objective get andevidence evaluation hits statement of action subject and transaction that economy value, to ascertaincompatibility level between statement referred [as] and criterion result that was established, and communicatereult to users that have interest (American Accounting Association). Audit is conducted by internal auditor andauditor external. Responsible Internal auditor to help the party of management improves effectivity andefesiensi organisasional, entered help design and mengimplementasikan Information system Akuntansi that givecontribution at company aims. External Auditor responsible at interested parties to company and investor,despite that indirectly have interest in Information system efectivity Accountany in company. Internal auditExistence in business organization (company) is to sufficiency evaluation and effectivity of operation systeminternal company, and specify facility from responsibility execution that really conducted. Type of internal auditactivity in company cover financial audit, information system audit and operational audit or management.Whereas audit processes covers step: plan, collect evidence, evidence evaluation and communicate audit resultto the party of management.Keywords: Audit Information System Accounting Bases on Computer